The relationship between the achievement goals and the burnout levels of collegiate cheerleaders - Manuel, Frenz Carlo B. 2001-
The study explores burnout levels and achievement goals among collegiate cheerleaders, aiming to determine the factors contributing to burnout and the relationship between burnout and achievement goals. Burnout was measured across three dimensions: exhaustion, reduced sense of accomplishment, and sports devaluation, while achievement goals were categorized into mastery-approach, mastery-avoidance, performance-approach, and performance-avoidance. A total of 46 collegiate cheerleaders participated in a survey designed to assess their burnout levels, achievement goals, and demographics. The findings revealed moderate burnout levels, with athletes who adopted mastery-approach goals experiencing less burnout than those with performance-avoidance goals. The study also explored the interplay between burnout and achievement goals, highlighting how these factors influence motivation and performance. Additionally, coping strategies, such as social support, rest, and maintaining a positive mindset, were identified as key factors in mitigating burnout. These results emphasize the importance of promoting mastery-based goals and providing effective coping strategies to prevent burnout in collegiate cheerleading teams.